Bacterial Dispersion Associated With Various Patient Face Mask Designs During Simulated Intravitreal Injections - Patel, Samir N.; Mahmoudzadeh, Raziyeh; Salabati, Mirataollah; Soares, Rebecca R.; Hinkle, John; Hsu, Jason; Garg, Sunir J.; Regillo, Carl D.; Ho, Allen C.; Cohen, Michael N.; Khan, M. Ali; Yonekawa, Yoshihiro; et al. (American journal of ophthalmology, 2021)
We sought to investigate bacterial dispersion with patient face mask use during simulated intravitreal injections. Prospective cross-sectional study. Fifteen healthy subjects were recruited for this single-center study. Each participant was instructed not to speak for 2 minutes, simulating a “no-talking” policy, while in an ophthalmic examination chair with an blood agar plate secured to the forehead and wearing various face masks (no mask, loose fitting surgical mask, tight-fitting surgical mask without tape, tight-fitting surgical mask with adhesive tape securing the superior portion of the mask, N95 mask, and cloth mask). Each scenario was then repeated while reading a 2-minute script, simulating a talking patient. The primary outcome measures were the number of colony-forming units (CFUs) and microbial species. During the “no-talking” scenario, subjects wearing a tight-fitting surgical mask with tape developed fewer CFUs compared with subjects wearing the same mask without tape (difference 0.93 CFUs [95% confidence interval 0.32-1.55]; P = .003). During the speech scenarios, subjects wearing a tight-fitting surgical mask with tape had significantly fewer CFUs compared with subjects without a face mask (difference 1.07 CFUs; P = .001), subjects with a loose face mask (difference 0.67 CFUs; P = .034), and subjects with a tight face mask without tape (difference 1.13 CFUs; P < .001). There was no difference between those with a tight-fitting surgical mask with tape and an N95 mask in the “no-talking” (P > .99) and “speech” (P = .831) scenarios. No oral flora were isolated in “no-talking” scenarios but were isolated in 8 of 75 (11%) cultures in speech scenarios (P = .02). The addition of tape to the superior portion of a patient's face mask reduced bacterial dispersion during simulated intravitreal injections and had no difference in bacterial dispersion compared with wearing N95 masks. •Patient face mask use may alter bacterial dispersion around the eye during intravitreal injections.•There was significantly more bacterial dispersion when wearing a tight-fitting face mask without tape compared with wearing a tight-fitting mask with tape.•There was no difference in bacterial dispersion between tight-fitting surgical masks with tape and N95 masks.•Taping the superior portion of a patient's face mask may limit bacterial dispersion when performing intravitreal injections.